Identification of a distinct cluster of GDF15high macrophages induced by in vitro differentiation exhibiting anti-inflammatory activities - Dai, Chaochao; Zhang, Hongyu; Zheng, Zhijian; Li, Chun Guang; Ma, Mingyuan; Gao, Haiqing; Zhang, Qunye; Jiang, Fan; Cui, Xiaopei (Frontiers in Immunology, 2024)
Macrophage-mediated inflammatory response may have crucial roles in the pathogenesis of a variety of human diseases. Growth differentiation factor 15 (GDF15) is a cytokine of the transforming growth factor-β superfamily, with potential anti-inflammatory activities. Previous studies observed in human lungs some macrophages which expressed a high level of GDF15. In the present study, we employed multiple techniques, including immunofluorescence, flow cytometry, and single-cell RNA sequencing, in order to further clarify the identity of such GDF15 high macrophages. We demonstrated that macrophages derived from human peripheral blood mononuclear cells and rat bone marrow mononuclear cells by in vitro differentiation with granulocyte-macrophage colony stimulating factor contained a minor population (~1%) of GDF15 high cells. GDF15 high macrophages did not exhibit a typical M1 or M2 phenotype, but had a unique molecular signature as revealed by single-cell RNA sequencing. Functionally, the in vitro derived GDF15 high macrophages were associated with reduced responsiveness to pro-inflammatory activation; furthermore, these GDF15 high macrophages could inhibit the pro-inflammatory functions of other macrophages via a paracrine mechanism. We further confirmed that GDF15 per se was a key mediator of the anti-inflammatory effects of GDF15 high macrophage. Also, we provided evidence showing that GDF15 high macrophages were present in other macrophage-residing human tissues in addition to the lungs. Further scRNA-seq analysis in rat lung macrophages confirmed the presence of a GDF15 high sub-population. However, these data indicated that GDF15 high macrophages in the body were not a uniform population based on their molecular signatures. More importantly, as compared to the in vitro derived GDF15 high macrophage, whether the tissue resident GDF15 high counterpart is also associated with anti-inflammatory functions remains to be determined. We cannot exclude the possibility that the in vitro priming/induction protocol used in our study has a determinant role in inducing the anti-inflammatory phenotype in the resulting GDF15 high macrophage cells. In summary, our results suggest that the GDF15 high macrophage cells obtained by in vitro induction may represent a distinct cluster with intrinsic anti-inflammatory functions. The (patho)physiological importance of these cells in vivo warrants further investigation.